2011
DOI: 10.1055/s-0031-1275658
|View full text |Cite
|
Sign up to set email alerts
|

Use of Anticholinergic Drugs in Patients with Schizophrenia in Asia from 2001 to 2009

Abstract: The wide variation in ACM prescription across Asia suggests that a combination of clinical, social, economic and cultural factors play a role in determining the use of these drugs. Regular reviews of ACM use are desirable to reveal the discrepancy between treatment guidelines and clinical practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
9
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 31 publications
3
9
0
1
Order By: Relevance
“…Equivocally, Chalks et al (2006) reported an increase in antipsychotic combination among female patients [31]. Our finding regarding the association between anti cholinergic agents use and antipsychotic combination is consistent with previous studies [22,32,33]. Antipsychotic combination is expected to be associated with higher CPZeq effects which explains the significant association between antipsychotic combination and use of anticholinergic agents [22].…”
Section: Discussionsupporting
confidence: 89%
“…Equivocally, Chalks et al (2006) reported an increase in antipsychotic combination among female patients [31]. Our finding regarding the association between anti cholinergic agents use and antipsychotic combination is consistent with previous studies [22,32,33]. Antipsychotic combination is expected to be associated with higher CPZeq effects which explains the significant association between antipsychotic combination and use of anticholinergic agents [22].…”
Section: Discussionsupporting
confidence: 89%
“…These studies have looked into national prescription patterns,[1] prescription patterns in general practice, and specialist care,[2] age, and gender differences in antipsychotic prescription,[3] prescription patterns of antidepressants,[4] mood stabilizers in bipolar disorder patients,[5] and rate of use of anti-cholinergic agents in psychiatric patients. [6] A few surveys of prescription patterns of various psychotropics from Asian centers too are available. [47]…”
Section: Introductionmentioning
confidence: 99%
“…Anticholinergics should be prudently prescribed because these drugs in addition to their well-known peripheral side-effects, may worsen positive symptoms, appear to partially ameliorate negative symptoms and are associated with impaired cognitive functioning of schizophrenic [10] and cognitive impairment in elderly patients [11]. A recent report [12] has confirmed that there is a wide variation in anticholinergic medication prescribing across various countries; a combination of clinical, social, economic and cultural factors are the determinants of the use of these drugs suggesting that there are considerable differences between treatment guidelines and clinical practice.…”
Section: Introductionmentioning
confidence: 99%